Maraval, Trinidad, B.W.I. - (:unkn) unknown (My University, 2010)
A view of the road leading to Maraval which is a valley in northern Trinidad.
Colour: Black and white; Style: Landscape; Other: Bordered; Divided
Keywords: Trinidad and Tobago; Postcards; Rural roads--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Maraval; Landscapes--Trinidad and Tobago; Views